THE HEALING POWER OF VOCAL MUSIC: ENHANCING POST-SURGICAL RECOVERY IN PATIENTS (CAHIERS MAGELLANES-NS, 2024)
This study investigates the impact of vocal music therapy on the healing process of post-surgical patients in Rewa District, Madhya Pradesh. Utilizing a randomized controlled trial, 100 participants were divided into two groups: an experimental group receiving vocal music therapy and a control group receiving standard care. Over a 4-week period, key physiological and psychological indicators—heart rate, cortisol levels, perceived stress, and pain scores—were measured at baseline and post-intervention. Statistical analyses, including paired t-tests and independent t-tests, revealed significant improvements in the experimental group. Patients exposed to vocal music therapy showed a substantial reduction in heart rate, cortisol levels, stress, and pain compared to the control group. The findings indicate that vocal music can effectively enhance physiological recovery and psychological well-being. This suggests the potential for integrating vocal music therapy into post-operative care, offering a non-invasive, cost-effective approach to improving patient outcomes in Rewa District.